Dissociative amnesia beyond the evidence about the functioning of memory - Manzanero, Antonio L.; Palomo, Rubén ([Madrid] : Colegio Oficial de Psicólogos de Madrid, 2020)
The reality of dissociative amnesia has been debated at length. From a clinical perspective, there is support for the existence of this phenomenon, with attempts to extrapolate it to legal contexts. However, there is little evidence to confirm it and, moreover, dissociative amnesias or repressed memories would go against evidences about the functioning of memory. The confusion between clinical psychology and forensic psychology, an inadequate definition of amnesia, the lack of a complete knowledge regarding the mechanisms of memory, and the problems inherent to the research of traumatic memories could explain the lack of agreement.
Descripción basada en Anuario de psicología jurídica, vol. 30 (2020), P. 43-46.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2023. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Amnesia disociativa; Guerras de la memoria; Memoria reprimida; Memoria traumática.; Artículos.